THE STUDY OF PATHOMORPHOLOGICAL DIAGNOSIS OF VITAL ORGANS AFTER MODERN TREATMENT OF DIABETIC FOOT SYNDROME - Ulugbek Yu. Ergashev; Adkhamjon R. Zokhirov; Khojimurod I. Ernazarov; Ravshankhuja R. Minavarkhyjayev; Behzod A. Abdusalomov (Central Asian Journal of Medicine, 2023)
Study of the effect of the new drug "Rheomannisol" on vital organs, taking into account pathomorphological aspects in the complex treatment of experimental diabetic foot syndrome.